Case Study of Attendance System Design Based on Web and Mobile - Zerach Jonathan, Raden Abel (Newinera Publisher, 2024)
The current problem is that the attendance process at SMA Negeri 1 Rantau Pulung is still done manually. This becomes a problem when the attendance book is lost or exposed to water, which causes the writing on the attendance book to become blurry. The impact that could occur if the attendance application is not made is that SMA Negeri 1 Rantau Pulung will continue to carry out the attendance process manually and could be affected by the problems mentioned previously. Another impact is being left behind in the field of technology in the current era of digitalization. The step in solving the problem was that the researcher contacted the principal of SMA Negeri 1 Rantau Pulung to offer a presence application, then the researcher asked for the data needed to build the presence application. The temporary results currently obtained are that the presence application has been successfully developed and can now carry out the attendance qrcode scanning process. The conclusion from the interim results of this research is that web and mobile based attendance applications have been successfully developed. The presence application can generate QR codes on the web and can scan the generated QR codes via a mobile application.